2022
DOI: 10.21037/atm-21-5924
|View full text |Cite
|
Sign up to set email alerts
|

A narrative review of research progress on the role of NLRP3 inflammasome in acne vulgaris

Abstract: Background and Objective: Acne vulgaris is a common skin disease around the world which affects the appearance of patients, as well as their physical and mental health. Cutibacterium acnes plays a vital role in the occurrence and development of acne vulgaris. Pattern recognition receptors (PRRs) are the first line of defense against external pathogens. The nucleotide oligomerization domain (NOD)-like receptor family pyrin containing 3 (NLRP3) inflammasome has recently been shown to contribute to the pathogenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Inflammasomes are large intracellular signaling complexes which initiate the inflammatory response. Some studies have shown that the nucleotide oligomerization domain (NOD)‐like receptor family pyrin containing 3 (NLRP3) inflammasome is linked to acne pathofisiology 26 . Some strains of P. acnes can activate the NLRP3 inflammasome and promote IL‐1β secretion 27 …”
Section: Resultsmentioning
confidence: 99%
“…Inflammasomes are large intracellular signaling complexes which initiate the inflammatory response. Some studies have shown that the nucleotide oligomerization domain (NOD)‐like receptor family pyrin containing 3 (NLRP3) inflammasome is linked to acne pathofisiology 26 . Some strains of P. acnes can activate the NLRP3 inflammasome and promote IL‐1β secretion 27 …”
Section: Resultsmentioning
confidence: 99%
“…These studies suggest that IL1R1 is a key factor in the development of skin inflammation, and acne belongs to chronic inflammatory diseases of the skin. It has been shown that porphyrins produced by Cutibacterium acnes activate NLRP3 inflammatory vesicles and promote IL-1β secretion ( 34 36 ). Therefore, we consider that the IL-1β-IL-1R signaling pathway may emerge as a key player in the developmental mechanism of severe acne.…”
Section: Discussionmentioning
confidence: 99%
“…Another recent review [120] explores the complex molecular pathways triggered in acne by pathogenic C. acnes strains via TLR and the activation by PAMPs and DAMPs (pattern/damage-associated molecular patterns) of PRRs (pattern recognition receptors) such as NOD (nucleotide-binding oligomerization domain) receptors and NLR (NOD-like receptors), with the subsequent assembly of the NLRP3 inflammasome, the activation of caspase-1 and the subsequent cascade of proinflammatory cytokines like IL-1β and IL-8. Some potentially useful inhibitors of this pathway, including NLRP3 inhibitors baicalein, eucalyptol extracted from Laurus nobilis, superoxide dismutases, auranofin (an antirheumatic colloidal gold compound), or ROS production inhibitor polyphyllin I may be successfully used in future therapeutic protocols for acne.…”
Section: Novel Therapeutic Approachesmentioning
confidence: 99%